Effect of shade on animal welfare, growth performance, and carcass characteristics in large pens of beef cattle fed a beta agonist in a commercial feedlot - Hagenmaier, Jacob A.; Reinhardt, Christopher D.; Bartle, Steven J.; Thomson, Daniel U. (My University, 2017)
Feedlot cattle (n = 1,395; BW = 568 +/- 43 kg) were used to evaluate the effects of shade on animal welfare, growth performance, and carcass quality during the summer of 2013 in a Kansas commercial feedlot. Seven lots of predominately black steers and heifers (4 and 3, respectively) visually determined to be approaching the final mo on feed were identified, randomly gate-sorted, and allocated to pens located across the feed alley from each other to receive 1 of 2 treatments: 1) Shade (mean shade area = 1.5 m(2)/animal) or 2) No shade. Shade was provided using a 13-ounce polyethylene fabric and pens were oriented northwest to southeast. The mean starting date was June 13 and the mean days on feed for lots while on the study was 38 d. Cattle were fed a 77.67% DM steam-flaked corn-based diet and had ad libitum access to water throughout the duration of the trial. Zilpaterol hydrochloride (ZIL) was included in the finishing ration at an inclusion rate of 8.3 mg/kg of DM for the last 20 d on feed with a 3 d withdrawal period. Pen floor temperatures (PFT) were measured using an infrared thermometer and prevalence of cattle open-mouth breathing (OMB) was recorded on a pen basis. In addition to shade treatment, the effect of temperature humidity index (THI) on PFT and OMB was analyzed by classifying days as either "Alert" (THI < 79) or "Danger" (THI > 79). On the day of slaughter, pens within a replicate were kept separate through all stages of the marketing channel from loading at the feedlot until stunning at the plant. Pen served as the experimental unit for all measurements. There was a THI x shade treatment interaction for PFT and OMB (P < 0.001) where days classified as "Danger" increased PFT and prevalence of OMB compared to "Alert" days in unshaded but not shaded cattle. Shaded cattle had greater DMI (P = 0.01); however, unshaded cattle had greater G:F (P = 0.05) and therefore no differences were observed in ADG (P = 0.39). Shaded cattle had greater dressing percentage (P = 0.01), although HCW, LM area, fat thickness, marbling score, and quality grade did not differ between treatments (P > 0.05). Heat stress, a significant animal welfare concern and cause of reduced performance in feedlot cattle during the final phase of the feeding period, was alleviated in shaded cattle and illustrates the importance of shade provision as 1 tool to protect the welfare and increase feed consumption in large pens of feedlot cattle during hot summer months.
Citation: Hagenmaier, J. A., Reinhardt, C. D., Bartle, S. J., & Thomson, D. U. (2016). Effect of shade on animal welfare, growth performance, and carcass characteristics in large pens of beef cattle fed a beta agonist in a commercial feedlot. Journal of Animal Science, 94(12), 5064-5076. doi:10.2527/jas2016-0935
Keywords: Beef Cattle; Growth Performance; Heat Stress; Shade; Welfare; Feeding Zilpaterol Hydrochloride